A comprehensive analysis of resilience processes in three MSMEs responding to accelerated digital transformation and operational challenges during the COVID-19 pandemic - Rizha, Teuku Muhamad; Machdum, Sari Viciawati (Interaction, Community Engagement, and Social Environment, 2025)
Background: This study focuses on the resilience of Micro, Small, and Medium Enterprises (MSMEs) in Tanjung Duren Utara, West Jakarta, in facing the challenges of the COVID-19 pandemic and the acceleration of digitalization. Methods: This study employs a qualitative and descriptive approach, focusing on three local MSMEs: Bakso Malang, Ayam Tulang Lunak 3 Saudara Cemara, and Mie Ayam Barokah. Through this approach, the research aims to identify and analyze the resilience processes demonstrated by MSMEs during the pandemic. Findings: The findings reveal that MSMEs undergo four stages of resilience: surrender, survival, recovery, and rapid growth. These stages involve adjustments to economic and psychological pressures, operational efficiency strategies, utilization of online delivery services, innovations in online marketing and customer service, and adaptation to digital technology. These findings are significant in highlighting how social support, personal strength, and the ability to act contribute to the success of MSMEs in facing the pandemic. Conclusion: Given the strategic role of MSMEs in the national economy, particularly in terms of labor absorption and contribution to the Gross Domestic Product, an analysis of their adaptation in this crisis situation is essential. Novelty/Originality of this article: The study underscores the importance of adaptation, innovation, and community support in building business resilience amidst uncertainty and challenges, demonstrating effective social functioning during the pandemic and avoiding social maladaptation.